Philosophical Views of Islamic Scholars on Free Will - Mammadova, Aygul (Scholarya Demo Journal of Ruby, 2019)
Free will is one of the important problems that Islamic philosophers debateover. It is philosophically main question that to which extent man as a part ofnature should be free in his actions. Different opinions exist about free will inother societies and beliefs. The concept of freedom is a phrase adopted byphilosophers.The article discusses the views about free will by the Islamic philosopherssuch as Kindi, Farabi, Ibn Sina, Ibn Rushd, Gazali and Nasreddin Tusicomparatively. The main aim of the research is to formulate a general idea onthe views of Islamic philosophers about free will and to analyze differences andsimilarities between their discourses. General overview of these philosophers’opinions reveal that they have accepted free will partially. The philosophersshare the similar opinions on the issues of free will, mind and will. On the onehand, they accept human as the one who is responsible for the actions, on theother hand, they accept Allah as a being limitless in power. According tophilosophers, a human being acts by free will and choice, thus, humans are freeas they choose their actions. They evaluate free will from the aspect of divinenature first and then from the aspect of human nature. Because existence ofhumans does not depend on themselves; it depends on God. Humans’implementation of choices through their free will depends on God’s power andthe will. The philosophers have accepted human will together with the will ofGod.